Combined Impacts of Genetic Variants of Long Non-Coding RNA MALAT1 and the Environmental Carcinogen on the Susceptibility to and Progression of Oral Squamous Cell Carcinoma - Ding, Yi-Fang; Wen, Yu-Ching; Chuang, Chun-Yi; Lin, Chiao-Wen; Yang, Yi-Chieh; Liu, Yu-Fan; Chang, Wei-Min; Chang, Lun-Ching; Yang, Shun-Fa; Chien, Ming-Hsien (Frontiers in Oncology, 2021)
Oral squamous cell carcinoma (OSCC) is the most common malignant tumor of the oral cavity, and long non-coding (lnc)RNA of metastasis-associated lung adenocarcinoma transcript 1 (MALAT1) was recently reported to play a crucial role in OSCC development and progression. However, potential effects of genetic variants of MALAT1 on the development of OSCC are still unclear. Herein, we performed a case-control study in 1350 patients with OSCC and 1199 healthy controls to evaluate the association between functional single-nucleotide polymorphisms (SNPs) of MALAT1 and OSCC susceptibility, as well as its clinicopathologic characteristics. A TaqMan allelic discrimination assay was used to genotype four tagging SNPs, viz., rs3200401 C>T, rs619586 A>G, rs1194338 C>A, and rs7927113 G>A, and results showed that the MALAT1 rs3200401 T allele had a lower risk of OSCC (adjusted odds ratio (AOR): 0.779, 95% confidence interval (CI): 0.632~0.960, p=0.019) and a higher risk of developing moderately (grade II)/poorly (grade III) differentiated OSCC (AOR: 1.508-fold, 95% CI: 1.049~2.169, p=0.027) under a dominant model. According to environmental carcinogen exposure, patients with a betel quid-chewing habit who carried the T allele of rs3200401 more easily developed high-grade (II/III) OSCC (AOR: 1.588, 95% CI: 1.055~2.390, p=0.027), and patients with the same genotype but who did not chew betel quid had a lower risk of developing lymph node metastasis (AOR: 0.437, 95% CI: 0.255~0.749, p=0.003). In addition to rs3200401, the rs619586 AG/GG genotype was associated with increased risks of developing advanced stages (III+IV) and larger tumor sizes (>T2) compared to the AA genotype, especially in the subgroup of betel quid chewers. Furthermore, analyses of clinical datasets revealed that the MALAT1 expression level was upregulated in OSCC compared to normal tissues, especially in the betel quid-chewing population. These results indicated involvement of MALAT1 SNPs rs3200401 and rs619586 in the development of OSCC and support the interaction between MALAT1 gene polymorphisms and the environmental carcinogen as a predisposing factor for OSCC progression.